Effect of Seeding Rates and Row Spacings on Fodder Production of Moth Bean ( Phaseolus acoritifolius) - Faroda, A S (Annals of Arid Zone, 2016)
( i) Seeding rates of 20 and 25 kg seed/ha produced significantly higher green and dry matter per hectare as compared to 15 kg seedha. The differences between 20 and 25 kg seed /ha were, however, non-significant. ( ii) Line sowing at a row spacing of 25 em was found to be significantly better than broadcasting and Line sowing at 50 Gm row spacings,